Popcorn days & buttermilk nights - Paulsen, Gary. (New York Puffin Books, 1989)
Carley recalls the extraordinary summer when, as a troubled fourteen-year-old, he first came to northern Minnesota to stay with his blacksmith Uncle David and gained not only new skills but also a new sense of himself.
Keywords: Uncles -- Fiction; Blacksmiths -- Fiction; Farm life -- Fiction; Minnesota -- Fiction